Chatbot Pelayanan Informasi Kampus - Saientisna, Detriasmita; Kadyanan, I Gusti Agung Gede Arya; Mahendra, Ida Bagus Made; Pradika, V.G.A. (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023DO - 10.24843/JNATIA.2023.v02.i01.p29, 2023)
As technology advances in the world of education, information about campuses becomes very important. Searching for information that is fast, precise, and easy is needed for prospective students, university students, other campus residents, and the public. Chatbots are the solution of choice because of their popularity. The use of chatbots is useful in finding information about campuses quickly and easily, where users no longer need to browse every website or go to campus officials to find out information. This chatbot can provide basic information about the services provided by the campus, information on study programs, faculties, and even campus officials.